The developing world is poorer than we thought, but no less successful in the fight against poverty - Chen, Shaohua, 1955- 1955- (Policy research working paper, 2008)
"The paper presents a major overhaul to the World Bank's past estimates of global poverty, incorporating new and better data. Extreme poverty-as judged by what "poverty" means in the world's poorest countries-is found to be more pervasive than we thought. Yet the data also provide robust evidence of continually declining poverty incidence and depth since the early 1980s. For 2005 we estimate that 1.4 billion people, or one quarter of the population of the developing world, lived below our international line of